DYNAMIC DNA: THE THREE ELEMENTS OF ORGANIZATIONAL AGILITY - ENTREPRENEURIAL ORIENTATION, COMPETITIVE INTELLIGENCE, AND STRATEGIC FLEXIBILITY - Mohammad Kalil Abraheem (Scholars Digest Publishing, 2023)
The study examines the potential relationship between entrepreneurial orientation, competitive intelligence, strategic flexibility and organizational agility at Al-Fadhel Al-Kabeer Company, a company based in Misan province in southern Iraq. The research utilizes a census method with a sample of 100 respondents and employs Smart PLS (Partial Least Square) for data analysis. The findings reveal positive relationships between entrepreneurial orientation, competitive intelligence, and strategic flexibility, as well as between these variables and organizational agility. The study highlights the importance of fostering an entrepreneurial culture, enhancing competitive intelligence capabilities, emphasizing strategic flexibility, and cultivating organizational agility for achieving and maintaining a competitive edge in dynamic business environments. Future research should expand the sample, explore additional variables, and investigate these relationships in diverse settings to enrich the understanding of the factors influencing organizational agility.
Keywords: Entrepreneurial Orientation, Competitive Intelligence, Strategic Flexibility, Organizational Agility.